Gaya Komunikasi Dosen dalam Pembelajaran Mahasiswa - Mutawakkil Mutawakkil; Nuraedah Nuraedah (Communicatus: Jurnal Ilmu komunikasi, 2019)
The research aims to analyze the communication style to overcome the boredom of studentsâ€™ learning in the social history course at History Education Program Study, Faculty of Teacher Training and Education, Tadulako University". This research uses qualitative research approach by examining 1 lecturer and 45 students in class A. Data analysis uses qualitative analysis, with three stages which include: data reduction, data presentation, and data verification.Â  The results of the research show that the communication style of lecturers to reduce boredom of learning, as follows: Develop an active communication style while still emphasizing assertiveness, taking full social initiative so that students can imitate and apply the communication style in their social environment, and they are able to express opinions with controlled emotions, communication style must be done in two-ways that is by sending full information attentively, communication style by commanding but showing the way, so that students become maximally measured in doing their tasks, there is reflection after evaluation, and communication style of the listener, being attentive in conveying information, making decisions by considering all parties.Penelitian bertujuan untuk menganalisis gaya komunikasi mengatasi kejenuhan Belajar pada matakuliah Sejarah Sosial Mahasiswa Pendidikan Sejarah Untadâ€. Dalam penelitian ini peneliti menekankan pada pendekatan kualitatif dengan meneliti 1 orang dosen dengan populasi mahasiswa 45 orang di kelas A. Analisis data dalam penelitian ini menggunakan analisis secara kualitatif, dengan tiga jenis meliputi: Reduksi Data, Penyajian data, serta Verifikasi data. Hasil peneitian menunjukkan: gaya komunikasi dosen untuk mengurangi kejenuhan belajar, sebagai berikut; mengembangkan gaya komunikasi aktif namun tetap mengedepankan ketegasan, mengambil secara penuh inisiatif sosial agar mahasiswa meniru di lingkungan sosialnya, serta mampu menyatakan pendapat dengan emosional yang terkontrol; gaya komunikasi harus dua arah dengan mengirim informasi secara full dengan penuh perhatian; gaya komunikasi dengan memerintah tapi menunjukkan caranya, sehingga mahasiswa menjadi terukur secara maksimal dapat mengerjakan tugas, ada refleksi ketika evaluasi, dan gaya komunikasiÂ  pendengar, penuh perhatian dalam menyampaikan informasi, membuat keputusan dengan mempertimbangkan semua pihak.